The Biological Welfare of Ibero-America - A New Anthropometric History
XXIV, 311 p. 59 illus.
Keywords: This book summarizes three decades of research in Iberian and Latin American anthropometric history, employing the most up-to-date methodologies in the field. Through a comparative and interdisciplinary approach, it examines the evolution of biological living standards in several Iberian and Latin American populations during the contemporary era, drawing on anthropometric data and its key determinants. The volume comprises nine long-term country studies—Argentina, Brazil, Chile, Colombia, Guatemala, Mexico, Peru, Portugal, and Spain—alongside an introduction and a comparative analysis. Being recognized experts on this field of study, the authors collectively display the knowledge gained in Anthropometric History in last twenty years. This edited collection highlights the value of anthropometric indicators for analyzing living standards and human well-being from a historical perspective and demonstrates the importance of interdisciplinary research in understanding human growth and biological welfare. Its findings explore the determinants of human physical development through various historical transitions, including nation-state formation, economic growth, and the expansion of public goods, as well as the long-term evolution of inequality in biological living standards across Iberian and Latin American contexts. Ricardo Salvatore is Professor of Modern History at Universidad Torcuato Di Tella, Buenos Aires (Argentina). His research focuses on living standards, social history, and inequality in Argentina and Latin America. Moramay López-Alonso is Associate Professor of History at Rice University, USA. Her work centers on economic history and living standards in Mexico and Latin America from an interdisciplinary perspective. Manuel Llorca-Jaña is Professor of Economic History at Universidad Adolfo Ibáñez, Chile. He specializes in global trade, economic history, and anthropometric studies in Chile and Latin America. José-Miguel Martínez-Carrión is Professor of Economic History at the University of Murcia, Spain. His research interests refer to nutritional change and biological well-being in Spain and Latin America.